The Tian Ma 65-m Telescope Automatic Early Warning System - Wei-Hua, Shang-Guan; Rong-Bing, Zhao; Dong, Zhang; Chu Yuan, Zhang (Frontiers in Astronomy and Space Sciences, 2022)
The Tian Ma Radio Telescope (TMRT), which is mainly used for deep space exploration and radio astronomy observations, is the largest fully steerable radio telescope in Asia. For promoting the automation of the telescope, an automatic early warning system is designed and implemented. The system can conveniently aggregate heterogeneous sensor data, make use of established strategies to implement an alert system, and send real-time alarms through multiple channels, which is helpful to promote unmanned operation. In addition, we adopt DevOps (a compound of development (Dev), and operations (Ops) means end-to-end automation in software development and delivery) to simplify the development, upgrading, and maintenance of the telescope automatic early warning system.